Audit Tenure, Specialization, and Timeliness in the Property Sector - Syarbini Ikhsan; Wukuf Dilvan Rafa (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to test the effect of operational complexity on audit report lag with auditor specialization as a moderating variable. High operational complexity is believed to extend audit completion time due to the increasing volume and complexity of information. Conversely, auditors with industry-specific expertise are expected to accelerate the audit process through a deeper understanding of the audited entity. This study uses a quantitative approach with multiple regression analysis and secondary data from company annual reports. Data is processed using SPSS, including classical assumption tests, t-tests, f-tests, and moderation interaction analysis. The results show that Audit Tenure does not significantly affect Audit Report Lag (significance = 0.992), nor does its interaction with Auditor Specialization show a significant moderating effect. However, the F-test shows that the overall regression model, including Audit Tenure, Auditor Specialization, and control variables, significantly affects Audit Report Lag (significance = 0.021). These findings suggest that although direct and moderating effects are not significant, the variables collectively contribute to explaining delays in audit reporting.